2020
DOI: 10.1128/aac.00236-20
|View full text |Cite
|
Sign up to set email alerts
|

AR-12 Exhibits Direct and Host-Targeted Antibacterial Activity toward Mycobacterium abscessus

Abstract: Therapeutic options for Mycobacterium abscessus infections are extremely limited. New or repurposed drugs are needed. The anti-M. abscessus activity of AR-12 (OSU-03012), reported to express broad-spectrum antimicrobial effects, was investigated in vitro and in vivo. Antimicrobial susceptibility testing was performed on 194 clinical isolates. Minimum bactericidal concentration and time-kill kinetics assays were conducted to distinguish the bactericidal versus bacteriostatic activity of AR-12. Synergy between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…abscessus ) and G71 ( M. abscessus subsp. abscessus ), in primary mouse peritoneal macrophages ( 16 ). The cells of both the experimental and control groups were washed three times with warm phosphate-buffered saline to remove the extracellular organisms.…”
Section: Contezolid Is Active Against M Abscessusmentioning
confidence: 99%
“…abscessus ) and G71 ( M. abscessus subsp. abscessus ), in primary mouse peritoneal macrophages ( 16 ). The cells of both the experimental and control groups were washed three times with warm phosphate-buffered saline to remove the extracellular organisms.…”
Section: Contezolid Is Active Against M Abscessusmentioning
confidence: 99%
“…An antibiotic was considered bactericidal when the MBC/MIC ratio was ≤4; otherwise, it was considered bacteriostatic. 15 …”
Section: Methodsmentioning
confidence: 99%
“…It was found that its structural analog, OSU‐03012 or AR‐12 (Figure 10), lacks the ability to inhibit cyclooxygenase‐2, but displays a number of other biological effects, including anticancer, antiviral and antibacterial activity 213‐215 . A recent study by Znang et al focused on its anti‐ M. abscessus activity, and the compound was shown to exhibit bactericidal activity with MIC values from 2 to 16 µg/L against 194 clinical M. abscessus isolates 216 . The compound showed an indifferent effect in combination with five antibiotics (clarithromycin, amikacin, imipenem, cefoxitin and tigecycline), that is, the bactericidal rate of the combinations was the same as those of the most active drug in each combination used individually.…”
Section: Interesting Early‐stage Small Molecules Active Against M Abscessus: From Bench To Bedside?mentioning
confidence: 99%